Knowledge, Practices, and Attitude of University Students towards the Prevention of Viral Respiratory Infection (COVID-19) - Crisa Sarte (San Beda University, 2020)
Background: COVID-19 has affected the educational system, particularly students of higher educational institutions. Accurate knowledge about the disease, its transmission, and preventive measures are critical for containing an outbreak. University students, the next generation of professionals, may play an imperative role in propagating key health information to society. Objectives: The study aims to assess the level of knowledge, the attitude of concern, and prevention practices among university students towards COVID-19 prevention. Methods: This descriptive study was conducted at a private higher educational institution in Central Luzon, Holy Angel University. 357 university students were recruited as study participants from the university's different departments using the purposive sampling method, and data were collected using an online self-administered questionnaire. Results: Among the 357 university students who completed the questionnaires, most were females (58.5%). The results show a good level of attitude of concern and good knowledge of clinical manifestations of COVID-19. The students' most frequently stated source of transmission is exposure to coughing and sneezing via droplets. Additionally, wearing face masks was the most reported method of protection against the infection. Conclusion: The study revealed that university students have adequate knowledge, practices, and attitude of concern towards COVID-19. To bridge the gap between current and required knowledge, it is essential to establish further professional educational campaigns to increase university students' awareness of the pandemic.